THE PANDEMIC INFLUENCE TO FIRM SIZE AND FINANCIAL RATIO ON LISTED COMPANIES IN THE HEALTHCARE INDUSTRY - Ramdhani, Rani; Mulyono, Mulyono; Wulandari, Respati (ULTIMA Management, 2023)
Abstract - During the pandemic, the government enacted policies that restricted people's travel, impacting corporate development across the board. The study's goal is to analyze the influence of the pandemic on firm size and financial ratios of companies listed on the Indonesia Stock Exchange in the Healthcare industry. Market capitalization statistics, return on assets, and debt to equity ratios were used as study samples. To assess the research hypothesis, the Wilcoxon sign rank test was performed. According to the findings of the study, return on assets decreased significantly during the pandemic, debt to equity ratio remained stable and did not vary significantly, and company size increased significantly during the pandemic. Companies in the post-pandemic period must pay close attention to the proper composition of funding sources in order to boost profitability and gain the trust of investors. Keywords: Debt to Equity; Financial Ratio; Firm Size; Pandemic Covid-19; Return on Asset